Comparison between diagnostic methods for the quantification of low-density lipoprotein in patients attended at a University Hospital - Wexlei Mendes Lopes, Robert (2019)
Introduction: Studies have reported a strong link between dyslipidemia and atherosclerosis. For this reason, exams such as the lipid profile are routinely performed for the prevention and monitoring of these diseases. Among the lipid indices, low density lipoproteins should be highlighted because due to their greater relation with risk factors for the development of atherosclerotic diseases. Therefore, direct methods of obtaining low density lipoproteins values, considered more accurate, are confronted with results usually obtained in the routine, through equations that provide estimated values. Objective: We compared the diagnostic methods used to obtain low density lipoproteins through the Friedewald and Martin formulas with the results obtained by automated methodology in patients attended at a University Hospital of Juiz de Fora – MG. Material and Methods: A total of 208 patients were recruited and venous blood samples were collected to obtain serum. The levels of total cholesterol, triglycerides and high density lipoprotein were quantified to obtain low density lipoproteins through the Friedewald and Martin equations. Results: A positive correlation between low density lipoproteins results has calculated by Martin and direct methods (ρ = 0.916), and positive correlation between Friedewald results and direct (ρ = 0.915). Discussion: We observed a positive correlation between the values of cholesterol and low density lipoproteins by the three methodologies. The Bland-Altman method has been used to compare the results obtained in search and methodology. Conclusion: Although the Friedewald and Martin equations have a good correlation with low density lipoproteins as measured by direct methodology, studies that relate atherosclerotic arterial diseases to low density lipoproteins should consider the direct quantification of this lipoprotein in order to cover individuals with their different specificities.